2015
DOI: 10.1063/1.4932162
|View full text |Cite
|
Sign up to set email alerts
|

A semi-flexible model prediction for the polymerization force exerted by a living F-actin filament on a fixed wall

Abstract: We consider a single living semi-flexible filament with persistence length p in chemical equilibrium with a solution of free monomers at fixed monomer chemical potential µ1 and fixed temperature T . While one end of the filament is chemically active with single monomer (de)polymerization steps, the other end is grafted normally to a rigid wall to mimick a rigid network from which the filament under consideration emerges. A second rigid wall, parallel to the grafting wall, is fixed at distance L << p from the f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Hence, Footer et al [21] used an optical trap set-up to measure the forces generated by the elongation of a few parallel-growing actin filaments in contact with a rigid microfabricated barrier, equilibrium being established between the bundle polymerization force and the trap restoring force directly proportional to the trap length. We observe that this set up represents in principle a true stable equilibrium state, as long as temperature and free monomer chemical potential are kept fixed and the implied chemical reactions are reversible with no filament escaping laterally along the obstacle wall [4,21,23]. Footer et al monitored the growth of approximately eight actin filaments and found a stationary force significantly smaller than the value predicted by Hill's theory.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Hence, Footer et al [21] used an optical trap set-up to measure the forces generated by the elongation of a few parallel-growing actin filaments in contact with a rigid microfabricated barrier, equilibrium being established between the bundle polymerization force and the trap restoring force directly proportional to the trap length. We observe that this set up represents in principle a true stable equilibrium state, as long as temperature and free monomer chemical potential are kept fixed and the implied chemical reactions are reversible with no filament escaping laterally along the obstacle wall [4,21,23]. Footer et al monitored the growth of approximately eight actin filaments and found a stationary force significantly smaller than the value predicted by Hill's theory.…”
mentioning
confidence: 98%
“…Actin filaments in cells are usually organized into fairly rigid bundles with the help of fascin, an actin cross-linking protein, while their growth is controlled by capping proteins, which prevent them from becoming too long and flexible [1]; due to these features and to the intrinsic large stiffness of these filaments, most of the existing models discard their flexibility and treat them as infinitely stiff. In this paper, following the lines set by [2][3][4], we investigate the role of flexibility in the process of reversible work production by F-actin filaments. Over the last decades, the underlying mechanism which enables cells to produce forces has been extensively studied, both theoretically and experimentally.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations